2003
DOI: 10.1161/01.atv.0000096655.56262.56
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-B2 Induces Migration of Endothelial Cells Through the Phosphatidylinositol-3 Kinase Pathway and Promotes Angiogenesis in Adult Vasculature

Abstract: Objective-Ephrin-B2 plays a key role in vascular development. The purpose of this study was to elucidate the molecular mechanisms of ephrin-B2 signaling through the EphB receptor in endothelial cells and to determine whether ephrin-B2 contributes to in vivo angiogenesis in adult mice. Methods and Results-A chemotaxis assay on a polycarbonate membrane revealed that ephrin-B2/Fc chimeric protein induced migration of human umbilical vein endothelial cells (HUVECs) at a level 98% greater than control (PϽ0.01).To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 33 publications
6
52
0
Order By: Relevance
“…Although the pathophysiological significance of the kidney development-related genes we examined is not fully clarified in diabetic nephropathy, ephrin B2, HIF 1␣, Pod-1, and GLEPP1 participate in various stages and aspects of glomerulogenesis and are relevant to some types of glomerular injury, as previously suggested (26). Ephrin B2 is a transmembrane ligand of the ephrin B2 receptor (Eph) and its signaling pathway is required for vascular morphogenesis (36,37) and glomerular microvascular assembly (27). HIF-1␣ is critical for renal vasculogenesis and glomerulogenesis (30), and nuclear localization of HIF-1␣ increases in murine adriamycin nephrosis (38).…”
Section: Discussionmentioning
confidence: 86%
“…Although the pathophysiological significance of the kidney development-related genes we examined is not fully clarified in diabetic nephropathy, ephrin B2, HIF 1␣, Pod-1, and GLEPP1 participate in various stages and aspects of glomerulogenesis and are relevant to some types of glomerular injury, as previously suggested (26). Ephrin B2 is a transmembrane ligand of the ephrin B2 receptor (Eph) and its signaling pathway is required for vascular morphogenesis (36,37) and glomerular microvascular assembly (27). HIF-1␣ is critical for renal vasculogenesis and glomerulogenesis (30), and nuclear localization of HIF-1␣ increases in murine adriamycin nephrosis (38).…”
Section: Discussionmentioning
confidence: 86%
“…9,12,14 -19 Reverse signaling via EphrinB2 stimulates migration and sprouting angiogenesis. 20 Growing evidence points to the expression of several Eph receptors in different cancer types. [21][22][23][24][25][26] The biological significance of this aberrant expression, however, is controversial.…”
mentioning
confidence: 99%
“…11,23 However, the regulation of successful vein graft adaptation to the arterial circulation, with just the "right amount" of wall thickening and dilation, without progression to neointimal hyperplasia and/or aneurysmal dilation, is not currently understood. 24 Downstream regulators of Eph-B4 signaling in the endothelial cell include Akt, ERK1/2 25,26 and caveolin-1. 8 Our finding that eNOS is phosphorylated with stimulation of Eph-B4 in adult venous endothelial cells is consistent with previous reports that have shown that activation of Eph-B4 enhances NO production in endothelial cells in vitro.…”
Section: Discussionmentioning
confidence: 99%